2024
DOI: 10.1371/journal.pone.0292689
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes of Asian cyprinid fishes: Novel insight into the chromosomal evolution of Labeoninae (Teleostei, Cyprinidae)

Sudarat Khensuwan,
Francisco de Menezes Cavalcante Sassi,
Renata Luiza Rosa de Moraes
et al.

Abstract: The Labeoninae subfamily is a highly diversified but demonstrably monophyletic lineage of cyprinid fishes comprising five tribes and six incertae sedis genera. This widely distributed assemblage contains some 48 genera and around 480 recognized species distributed in freshwaters of Africa and Asia. In this study, the karyotypes and other chromosomal properties of five Labeoninae species found in Thailand Labeo chrysophekadion (Labeonini) and Epalzeorhynchos bicolor, Epalzeorhynchos munense, Henicorhynchus siam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Differentiated sex chromosomes seem rare, with only one ZZ/ZW case described for Squalius recurvirostris [ 24 26 ]. Recently, a study combining molecular and classical cytogenetics revealed that the sister tribe Labeonini have a conserved 2n but with extensive structural chromosome rearrangements [ 27 ]. Thus, the aim of the present study was to provide the first finer-scale cytogenetic investigation in cyprinids from the Systomini tribe using both by conventional (Giemsa staining and Ag-NOR) and molecular (fluorescence in situ hybridization (FISH) with 5S and 18S rDNA probes) methods in 15 species.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiated sex chromosomes seem rare, with only one ZZ/ZW case described for Squalius recurvirostris [ 24 26 ]. Recently, a study combining molecular and classical cytogenetics revealed that the sister tribe Labeonini have a conserved 2n but with extensive structural chromosome rearrangements [ 27 ]. Thus, the aim of the present study was to provide the first finer-scale cytogenetic investigation in cyprinids from the Systomini tribe using both by conventional (Giemsa staining and Ag-NOR) and molecular (fluorescence in situ hybridization (FISH) with 5S and 18S rDNA probes) methods in 15 species.…”
Section: Introductionmentioning
confidence: 99%